The Lahu Minority in Southwest China : a Response to Ethnic Marginalization on the Frontier. - Ma, Jianxiong (Routledge contemporary China series., 2013)
The Lahu, with a population of around 470,000, inhabit the mountainous country in Yunnan Province bordering on Burma, Laos and northern Thailand. Buddhists, with a long history of resistance to the Chinese Han majority, the Lahu are currently facing a serious collapse of their traditional social system, with the highest suicide rate in the world, large scale human trafficking of their women, alcoholism and poverty. This book, based on extensive original research including long-term anthropological research among the Lahu, provides an overview of the traditional way of life of the Lahu, thei.